2020
DOI: 10.52547/jhsme.7.3.65
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Role of Religiosity in the Relationship between Occupational Stress and Marital Satisfaction in Female Nurses

Abstract: Background and Objectives: Marital satisfaction is one of the factors that are related to mental health and occupational stress in nurses. Many studies have shown that religiosity is associated with greater stability and higher quality of marital life. In this regard, the present study aimed to investigate the modulating role of religiosity on occupational stress in female nurses and their marital satisfaction.Methods: This descriptive-analytical research was performed on female nurses working in hospitals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…In this study, marital satisfaction was moderate, which is almost similar to the marital satisfaction of Iranian people in general (22). Our results were in line with previous studies that examined the quality of life in Iranian nurses (14,23). A study in China reported that Chinese nurses' marital satisfaction was lower than that of the general population (18).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, marital satisfaction was moderate, which is almost similar to the marital satisfaction of Iranian people in general (22). Our results were in line with previous studies that examined the quality of life in Iranian nurses (14,23). A study in China reported that Chinese nurses' marital satisfaction was lower than that of the general population (18).…”
Section: Discussionsupporting
confidence: 89%